Upper Respiratory Tract Microbial Communities, Acute Otitis Media Pathogens, and Antibiotic Use in Healthy and Sick Children - Pettigrew, Melinda M. (American Society for Microbiology, 2012)
The composition of the upper respiratory tract microbial community may influence the risk for colonization by the acute otitis media (AOM) pathogens Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. We used culture-independent methods to describe upper respiratory tract microbial communities in healthy children and children with upper respiratory tract infection with and without concurrent AOM. Nasal swabs and data were collected in a cross-sectional study of 240 children between 6 months and 3 years of age. Swabs were cultured for S. pneumoniae, and real-time PCR was used to identify S. pneumoniae, H. influenzae, and M. catarrhalis. The V1-V2 16S rRNA gene regions were sequenced using 454 pyrosequencing. Microbial communities were described using a taxon-based approach. Colonization by S. pneumoniae, H. influenzae, and M. catarrhalis was associated with lower levels of diversity in upper respiratory tract flora. We identified commensal taxa that were negatively associated with colonization by each AOM bacterial pathogen and with AOM. The balance of these relationships differed according to the colonizing AOM pathogen and history of antibiotic use. Children with antibiotic use in the past 6 months and a greater abundance of taxa, including Lactococcus and Propionibacterium, were less likely to have AOM than healthy children (odds ratio [OR], 0.46; 95% confidence interval [CI], 0.25 to 0.85). Children with no antibiotic use in the past 6 months, a low abundance of Streptococcus and Haemophilus, and a high abundance of Corynebacterium and Dolosigranulum were less likely to have AOM (OR, 0.51; 95% CI, 0.31 to 0.83). An increased understanding of polymicrobial interactions will facilitate the development of effective AOM prevention strategies.